2018
DOI: 10.3389/fimmu.2018.01328
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Dendritic Cells Differentiated in the Presence of Lenalidomide Display a Semi-Mature Phenotype, Enhanced Phagocytic Capacity, and Th1 Polarization Capability

Abstract: Lenalidomide is an analog of thalidomide, with potent anticancer activity demonstrated in several hematological malignancies. It has immunomodulatory properties, being able to enhance the activation of different types of immune cells, which results in antitumor activities. Dendritic cells (DCs) are pivotal in the immune response, and different immunotherapeutic approaches targeting these cells are being developed. Since little is known about the effect of lenalidomide on DCs, the goal of the present work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Immature moDCs are also potent phagocytes, can cross-present antigens, inhibit T cell proliferation and increase regulatory cells which are crucial for immune tolerance and protection against autoimmune diseases [ 36 , 42 , 43 , 44 , 45 ]. In a study by Qu et al, LSF was shown to inhibit the maturation of immature porcine-derived moDC while increasing their phagocytic capacity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immature moDCs are also potent phagocytes, can cross-present antigens, inhibit T cell proliferation and increase regulatory cells which are crucial for immune tolerance and protection against autoimmune diseases [ 36 , 42 , 43 , 44 , 45 ]. In a study by Qu et al, LSF was shown to inhibit the maturation of immature porcine-derived moDC while increasing their phagocytic capacity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of monocytes/macrophages that phagocytosed at least one type of bacteria in the total monocyte/macrophage population is taken as the phagocytosis rate. Phagocytic index is defined as the average number of bacteria in phagocytic cells which was quantified in flow cytometer by the mean channel of fluorescence (Juan et al, 2018). In order to test the universality of the phagocytosis effect of succinate on monocytes/macrophages, gram-negative or gram-positive bacteria including E. tarda, S. agalactiae, and S. iniae were selected for phagocytosis in vitro.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…3 ). 88 MARCH 1 has also been documented to be regulated by itself through dimerization and autoubiquitination. 89 However, another study reported contradictory results, that the ubiquitination and degradation of MARCH 1 are mediated by an unknown E3 ligase with the help of ubiquitin-conjugating enzyme E2 D1 (Ube2D1), rather than MARCH 1 itself.…”
Section: Targeting Immune Checkpoint Pathways Via the Regulation Of Umentioning
confidence: 99%
“…For example, the E3 agonist BM that targets SLIM has shown therapeutic efficacy in a mouse model of autoimmune encephalomyelitis; 133 oridonin, which targets FBW7, induces cancer cell apoptosis and overcomes resistance to targeted therapy. 26 The E3 inhibitor lenalidomide, which targets MARCH 1, has been used to treat hematologic malignancies; 88 the DUB inhibitor curcumin destabilizes CSN5 and improves the efficacy of immunotherapy in breast cancer, melanoma, and colon cancer; 53 P5091, which targets USP7, induces apoptosis in multiple myeloma cell lines. 134 Given the success of these E3 inhibitors and DUB inhibitors, increasing efforts have been made to design and develop novel small molecule inhibitors that are expected to modulate immune checkpoint pathways.…”
Section: Targeting Immune Checkpoint Pathways Via the Regulation Of Umentioning
confidence: 99%